Lightweight and flexible hardware implementation of authenticated encryption algorithm SIMON‐Galois/Counter Mode - Cheng, Xin; Xu, Yixuan; Wang, Kefan; Zhang, Yongqiang; Li, Bin; Zhang, Zhang (International journal of circuit theory and applications, 2023)
Summary This brief proposes a new lightweight authenticated encryption algorithm SIMON‐GCM for Internet of Things (IoT) security, which realizes the combination of SIMON block cipher and Galois/Counter Mode (GCM). The designed SIMON circuit supports 128/192/256‐bit key size, which improves the flexibility and enlarges the range of applications. Moreover, the scheme of 32‐cycle Galois field (GF) multiplier in GF(2128) is adopted to effectively reduce the hardware cost of the Galois Hash (GHASH) function in GCM. At the same time, a finite state machine (FSM) is used to run the SIMON and GHASH modules in parallel, thus shortening the authenticated encryption time. The whole circuit is designed and implemented in field programmable gate array (FPGA) platforms. It is measured to yield a throughput of 32.4 Gbps when consuming 331 slices in Artix‐7. Compared with the existing authenticated encryption algorithms, the proposed algorithm achieves lower resource consumption and better flexibility. This paper proposes a new lightweight authenticated encryption algorithm SIMON‐GCM, which realizes the combination of SIMON block cipher and Galois/Counter Mode (GCM). The designed SIMON circuit supports multi‐key size with flexibility, the scheme of 32‐cycle Galois field (GF) multiplier in GF(2128) is adopted to reduce the hardware cost, and a finite state machine (FSM) is used to run the SIMON and GHASH modules in parallel to shorten the authenticated encryption time.